Workplace ostracism and turnover intention among executives in Malaysia’s e-commerce companies: Psychological capital as a moderator - Tee, Geok Hong (2024)
High employee turnover is a significant concern for most organizations, including E-commerce companies in Malaysia. Workplace ostracism could increase turnover intention, while psychological capital can enhance employees’ mental health and buffer the harmful effects of workplace ostracism on turnover intention. This study investigates the association between workplace ostracism and turnover intention among executives in Malaysia’s E-commerce companies by considering psychological capital as a moderator. This study used a quantitative-based cross-sectional survey design. A total of 160 respondents, consisting of 52.5% female and 47.5% male executives who worked in Malaysia’s E-commerce companies, with a mean age of 27.89 years old, were recruited through an unrestricted self-selected survey method with specific criteria. An online questionnaire comprising the Workplace Ostracism Scale (WOS-10), Psychological Capital Questionnaire (PCQ-24), and Turnover Intention Scale (TIS-6) was distributed to the targeted respondents via LinkedIn. The data collected was analyzed using Pearson’s Product-Moment Correlation, Hierarchical Multiple Linear Regression, and Hayes’ SPSS Process Macro (Model 1). The results showed a significant positive association between workplace ostracism and turnover intention, while a significant negative association between psychological capital and turnover intention. However, psychological capital does not moderate the association between workplace ostracism and turnover intention. This study raises awareness among employers in Malaysia’s E-commerce companies to take proactive action to tackle workplace ostracism. This study also highlights the importance of conducting psychological capital workshops to reduce turnover intention among executives in Malaysia’s E-commerce companies.